Encontro, condução e costura: a f(r)icção entre o diretor e o ator social nos documentários - Segundo, Carlos Antonio dos Santos (2011)
The contact with the documentary production as director, turns out to put myself in a privileged place within the conceptual construction on this genre of film. Being face to face with the character and to experience its importance in the process of producing a movie made me understand from a different point of view the stages of conception of artistic work. Therefore, this research seeks to understand, supported by the psychoanalytic method of interpretation, these three specific moments - meeting, conduction and sewing - of fundamental importance for the documentary film. The director and the character within a relationship of f (r)iction, put their subjectivities in constant shock, and it is precisely this friction and the different paths that arises is what provides the uniqueness of this mode of film production as complex and full of nuances. What the camera captures is something beyond mere likeness, representation and enactment of those who cross their objective. In the skin, under the skin of film, there is also a psychic wide world that this research tries to highlight.